Psychotic symptoms due to topiramate - Gülay Oğuz; Mükerrem Güven; Saime Çağlı; Sedat Batmaz (Psychiatria i Psychologia Kliniczna, 2015)
Topiramate is an antiepileptic drug prescribed in the treatment of numerous psychiatric disorders and in epilepsy. Topiramate exerts its antiepileptic effect through different mechanisms, such as by the blockage of sodium channels, increasing GABAergic neurotransmission, antagonizing excitatory amino acid receptors (glutamate) or blocking calcium channels. Its prescription in psychiatric diseases has increased in recent years and psychotic symptom development due to the usage of topiramate has been observed in some studies. Therefore, it is essential to evaluate the patient for psychotic symptoms while using topiramate. This article presents a case of a 37-year-old woman who developed depression, anxiety and auditory hallucinations during the treatment with 150 mg of topiramate. After stopping topiramate, 5 mg of olanzapine bid was started and the symptoms gradually decreased and finally disappeared.